PERENCANAAN BENDUNGAN SALAK KABUPATEN KULON PROGO, YOGYAKARTA - Aprilia Cheni Hermawati; Arinda Puspitaningtyas; Suseno Darsono; Sugiyanto Sugiyanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Increasement of water demand that caused from the population increasement and land use change over at Progo Basin, inversely with water supply to that area. So that, the solution to conquer the problem is to build a water reservoir. One of the alternative is Salak Dam which located at Kalibawang District, Kulon Progo Regency, Yogyakarta. Salak Dam is a vertical core earthfill dam, which built on Salak River with 9.4 km2 of catchment area. This dam aims to fulfill public water supply and watering three fields area and designed with 100 years of return period with inflow discharge valued 46.9 m3/second. Salak Dam designed 48.5 meters of height, with 18.5 million cubic meters of capacity. This dam equipped with 2.2 meters of diameter outlet pipe, Ogee type of spillway with 20 meters of width, and USBR III of stilling basin. Construction of Salak Dam costs around 450 billion Rupiahs and scheduled for 39 weeks.